Crown ether derived from d-glucose as an efficient phase-transfer catalyst for the enantioselective Michael addition of malonates to enones. Issue 19 (15th October 2016) - Rapi, Zsolt; Grün, Alajos; Nemcsok, Tamás; Hessz, Dóra; Kállay, Mihály; Kubinyi, Miklós; Keglevich, György; Bakó, Péter
Graphical abstract: Abstract: A monoaza-15-crown-5 lariat ether derived fromd -glucose1 has been applied as a chiral phase-transfer catalyst in the Michael addition of diethyl, dimethyl, diisopropyl and dibenzyl malonates to enones under mild conditions to afford the adducts with good to excellent enantioselectivities. In the reaction of diethyl malonate with substituted trans -chalcone, the adducts with in enantioselectivities up to 89% ee. Among the reactions of substituted diethyl malonates, those of diethyl acetoxymalonate gave the best results (96% ee). The effect of the substituents of the chalcone was also investigated in reactions with diethyl acetoxymalonate. Among the chalcones substituted on the β-aryl, the para -substituted compounds resulted in the highest enantioselectivities (88–97% ee). The substituents on the benzoyl aryl of chalcone caused a decrease in the enantioselectivity compared to the unsubstituted case. The adducts with furyl or thiophenyl substituents were formed with >99% ee. The glucose-based catalyst also proved to be effective in the cases of diisopropyl and dibenzyl acetoxymalonates (including ees up to 99% ee). The reactions of diethyl acetoxymalonate with cyclic enones gave the corresponding Michael adducts with enantioselectivities up to 83%. The absolute configuration of one of the new Michael adducts was determined by CD spectroscopy. Abstract : (+)-Diethyl-2-(3-oxo-1, 3-diphenylpropyl)malonate: C22 H24 O5 Ee 36% (chiral HPLC) [ α ]D 22 = +17 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: ( S ) Abstract : (+)-Diethyl-2-(1-(2-methyoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C23 H26 O6 Ee 24% (chiral HPLC) [ α ]D 22 = +13 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-(1-(3-methyoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C23 H26 O6 Ee 25% (chiral HPLC) [ α ]D 22 = +18.6 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-(1-(4-methyoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C23 H26 O6 Ee 89% (chiral HPLC) [ α ]D 22 = +17.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-(1-(2-chlorophenyl)-3-oxo-3-phenylpropyl)malonate: C22 H23 ClO5 Ee 27% (chiral HPLC) [ α ]D 22 = +14.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-(1-(3-chlorophenyl)-3-oxo-3-phenylpropyl)malonate: C22 H23 ClO5 Ee 36% (chiral HPLC) [ α ]D 22 = +15.2 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-(1-(4-chlorophenyl)-3-oxo-3-phenylpropyl)malonate: C22 H23 ClO5 Ee 85% (chiral HPLC) [ α ]D 22 = +11.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetamido-2-(3-oxo-1, 3-diphenylpropyl)malonate: C24 H27 NO6 Ee 46% (chiral HPLC) [ α ]D 22 = +6.7 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-methyl-2-(3-oxo-1, 3-diphenylpropyl)malonate: C23 H26 O5 Ee 31% (chiral HPLC) [ α ]D 22 = +19.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-allyl-2-(3-oxo-1, 3-diphenylpropyl)malonate: C25 H28 O5 Ee 63% (chiral HPLC) [ α ]D 22 = +18.5 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-oxo-1, 3-diphenylpropyl)malonate: C24 H26 O7 Ee 96% (chiral HPLC) [ α ]D 22 = +15.6 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: S Abstract : (+)-Diethyl-2-acetoxy-2-(1-(2-methoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C25 H28 O8 Ee 39% (chiral HPLC) [ α ]D 22 = +22.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(3-methoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C25 H28 O8 Ee 72% (chiral HPLC) [ α ]D 22 = +15.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(4-methoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C25 H28 O8 Ee 97% (chiral HPLC) [ α ]D 22 = +17.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(2-chlorophenyl)-3-oxo-3-phenylpropyl)malonate: C24 H25 ClO7 Ee 15% (chiral HPLC) [ α ]D 22 = +14.6 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(3-chlorophenyl)-3-oxo-3-phenylpropyl)malonate: C24 H25 ClO7 Ee 81% (chiral HPLC) [ α ]D 22 = +14.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(4-chlorophenyl)-3-oxo-3-phenylpropyl)malonate: C24 H25 ClO7 Ee 88% (chiral HPLC) [ α ]D 22 = +13.6 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(2-nitrophenyl)-3-oxo-3-phenylpropyl)malonate: C24 H25 NO9 Ee 72% (chiral HPLC) [ α ]D 22 = +14.7 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(3-nitrophenyl)-3-oxo-3-phenylpropyl)malonate: C24 H25 NO9 Ee 81% (chiral HPLC) [ α ]D 22 = +20.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(4-nitrophenyl)-3-oxo-3-phenylpropyl)malonate: C24 H25 NO9 Ee 89% (chiral HPLC) [ α ]D 22 = +13.8 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(1-(naphthalen-2-yl)-3-oxo-3-phenylpropyl)malonate: C28 H28 O7 Ee 52% (chiral HPLC) [ α ]D 22 = +32.4 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl 2-acetoxy-2-(3-oxo-3-phenyl-1-(thiophen-2-yl)propyl)malonate: C22 H24 O7 S Ee 33% (chiral HPLC) [ α ]D 22 = +13.7 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl 2-acetoxy-2-(3-oxo-3-phenyl-1-(pyridin-3-yl)propyl)malonate: C23 H25 NO7 Ee 36% (chiral HPLC) [ α ]D 22 = +16.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(2-nitrophenyl)-3-oxo-1-phenylpropyl)malonate: C24 H25 NO9 Ee 2% (chiral HPLC) [ α ]D 22 = +0.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(3-nitrophenyl)-3-oxo-1-phenylpropyl)malonate: C24 H25 NO9 Ee 7% (chiral HPLC) [ α ]D 22 = +2.8 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(4-nitrophenyl)-3-oxo-1-phenylpropyl)malonate: C24 H25 NO9 Ee 58% (chiral HPLC) [ α ]D 22 = +1.3 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(2-chlorophenyl)-3-oxo-1-phenylpropyl)malonate: C24 H25 ClO7 Ee 33% (chiral HPLC) [ α ]D 22 = +12.0 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(3-chlorophenyl)-3-oxo-1-phenylpropyl)malonate: C24 H25 ClO7 Ee 31% (chiral HPLC) [ α ]D 22 = +13.0 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(4-chlorophenyl)-3-oxo-1-phenylpropyl)malonate: C24 H25 ClO7 Ee 26% (chiral HPLC) [ α ]D 22 = +3.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(2-methoxyphenyl)-3-oxo-1-phenylpropyl)malonate: C25 H28 O8 Ee 27% (chiral HPLC) [ α ]D 22 = +11.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(3-methoxyphenyl)-3-oxo-1-phenylpropyl)malonate: C25 H28 O8 Ee 96% (chiral HPLC) [ α ]D 22 = +7.0 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(4-methoxyphenyl)-3-oxo-1-phenylpropyl)malonate: C25 H28 O8 Ee 59% (chiral HPLC) [ α ]D 22 = +16.8 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (-)-Diethyl-2-acetoxy-2-(3-(naphthalene-1-yl)-3-oxo-1-phenylpropyl)malonate: C28 H28 O7 Ee 28% (chiral HPLC) [ α ]D 22 = −7.6 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-(naphthalene-2-yl)-3-oxo-1-phenylpropyl)malonate: C28 H28 O7 Ee 45% (chiral HPLC) [ α ]D 22 = +41.7 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl 2-acetoxy-2-(3-(furan-2-yl)-3-oxo-1-phenylpropyl)malonate: C22 H24 O8 Ee 99% (chiral HPLC) [ α ]D 22 = +10.5 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl 2-acetoxy-2-(3-(thiophen-2-yl)-3-oxo-1-phenylpropyl)malonate: C22 H24 O7 S Ee 99% (chiral HPLC) [ α ]D 22 = +13.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Dimethyl-2-acetoxy-2-(3-oxo-1, 3-diphenylpropyl)malonate: C22 H22 O7 Ee 61% (chiral HPLC) [ α ]D 22 = +16.2 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diisopropyl-2-acetoxy-2-(3-oxo-1, 3-diphenylpropyl)malonate: C26 H30 O7 Ee 92% (chiral HPLC) [ α ]D 22 = +15.7 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Dibenzyl-2-acetoxy-2-(3-oxo-1, 3-diphenylpropyl)malonate: C34 H30 O7 Ee 34% (chiral HPLC) [ α ]D 22 = +16.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Dimethyl-2-acetoxy-2-(1-(4-methoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C23 H24 O8 Ee 17% (chiral HPLC) [ α ]D 22 = +20.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diisopropyl-2-acetoxy-2-(1-(4-methoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C27 H32 O8 Ee 35% (chiral HPLC) [ α ]D 22 = +18.6 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Dibenzyl-2-acetoxy-2-(1-(4-methoxyphenyl)-3-oxo-3-phenylpropyl)malonate: C35 H32 O8 Ee 99% (chiral HPLC) [ α ]D 22 = +18.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-oxocyclopentyl)malonate: C14 H20 O7 Ee 46% (chiral HPLC) [ α ]D 22 = +0.5 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-oxocyclohexyl)malonate: C15 H22 O7 Ee 80% (chiral HPLC) [ α ]D 22 = +3.9 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined Abstract : (+)-Diethyl-2-acetoxy-2-(3-oxocyclohexyl)malonate: C23 H24 O5 Ee 83% (chiral HPLC) [ α ]D 22 = +8.1 ( c 1, CHCl3 ) Source of chirality: asymmetric synthesis by chiral catalyst Absolute configuration: not determined